Recent trends in barbiturate detection in medicolegal deaths. (November 2021) - Stephenson, Lilli; Kenneally, Michaela; van den Heuvel, Corinna; Humphries, Melissa; Stockham, Peter; Byard, Roger W.
Highlights: 51 cases had barbiturates were detected in post-mortem blood samples from 2000 to 2019. In 17 cases, barbiturate toxicity was the primary cause of death. Barbiturates were obtained by online purchase from overseas (N = 9; 33%), and through veterinary practice (N = 2; 7%). Deaths primarily due to barbiturate toxicity rose from 1 in 2000–2004 to 9 in 2015–2019. However, 23 of the deaths (45%) were due to natural causes in individuals prescribed barbiturates for epilepsy. Abstract: A study was undertaken of 51 cases where barbiturates were detected in post-mortem blood samples from 2000 to 2019 at Forensic Science South Australia, Adelaide, Australia. The cause of death was drug toxicity in only 27 (53%) (M:F = 19:8; age range 19-74yrs, mean 46yrs). In 17 cases, barbiturate toxicity was the primary cause of death, 14 due to pentobarbitone and 3 to phenobarbitone. All were suicides. Barbiturates were obtained by online purchase from overseas sources in 9 cases (33%), and through veterinary practice in 2 cases (7%). Drug toxicity deaths where barbiturates were detected rose from 1 in 2000–2004 to 11 in 2015–2019, and those where deaths were primarily due to barbiturate toxicity rose from 1 in 2000–2004 to 9 in 2015–2019. However, the mere detection of barbiturates in post mortem samples did not equate with illicit use, as 23 of the deaths (45%) were due to natural causes in individuals prescribed barbiturates for epilepsy. The usefulness of examining subset populations separate from accrued national data is also demonstrated in the significantly younger age of decedents in South Australia dying from deliberately administered barbiturates (46 yrs) compared to the national average of 57.9 yrs. The reasons for this difference will require further investigation as this may impact upon local suicide prevention strategies.